2018
DOI: 10.14740/gr1006w
|View full text |Cite
|
Sign up to set email alerts
|

Denture-Associated Oral Microbiome and Periodontal Disease Causing an Anaerobic Pyogenic Liver Abscess in an Immunocompetent Patient: A Case report and Review of the Literature

Abstract: Pyogenic liver abscesses (PLA) develop from the spread of infection through the portal circulation, biliary infections or arterial hematogenous seeding in the setting of systemic infections. PLA are often poly-microbial and are uncommonly reported to be due to anaerobic species. We report the case of a previously healthy, immunocompetent 63-year-old man with hepatic abscesses as a result of Fusobacterium nucleatum periodontal disease. In addition, a systemic review of the literature is performed. Fusobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“… 3 It has been reported that individuals with diabetes are at 3.6 times greater risk for PLA and 43% of patients have underlying biliary disease. 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 It has been reported that individuals with diabetes are at 3.6 times greater risk for PLA and 43% of patients have underlying biliary disease. 4 …”
Section: Discussionmentioning
confidence: 99%
“… 4 While in Asian populations Klebsiella pneumonia has been shown to be the predominant pathogen. 4 Fusobacterium nucleatum has been identified as a rare cause of PLAs in the literature. These patients are usually immunocompromised, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two main types of liver abscess exist: PLA is the most common type in the USA and amoebic liver abscess is the more prevalent type in developing countries. Pathogenesis is thought to involve spread through the portal circulation from related organs, direct spread from the biliary tract infections or hematogenous seeding from an extra-portal infectious source with dental infections being one of the recognised sources 5. A large retrospective study of PLA looking into 18 000 patients reported an incidence of 3.6 cases per 100 000 inhabitants in the USA 6.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of literature, we identified only 12 cases of F. nucleatum monomicrobial PLA in immunocompetent cancer-free hosts in the English literature (table 1). 3 5 8–17 Only one of those patients was diabetic. Four patients (33.3%) had a single abscess with the remainder of cases having multiple hepatic abscess.…”
Section: Discussionmentioning
confidence: 99%